2014
DOI: 10.1097/ccm.0b013e3182a639fd
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Impairs Neurogenesis and Neurologic Recovery and Increases Mortality Rate in Adult Rats After Traumatic Brain Injury*

Abstract: The results show that propofol may prevent or limit reparative processes in the early-phase postinjury. The results therefore indicate that anesthetics may be potentially harmful not only in very young mammalians but also in adult animals following acute cerebral injuries. The results provide first evidence for an altered sensitivity for anesthesia-related negative effects on neurogenesis, functional outcome, and survival in adult rats with brain lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 36 publications
0
34
2
Order By: Relevance
“…Anesthetic agents acting via GABA A receptors are frequently used in these patients’ anesthesia to induce and maintain general anesthesia. [30] Drexel and coworkers assessed the expression of GABA A receptor subunit mRNAs in rats 6 hours and 4 months post-TBI in the hippocampus and thalamus. [31] In the hippocampus the expression of α1-, α2-, α5-, β2-, β3- γ2- and δ- GABA A receptor subunit mRNAs were down-regulated 6 and 24 hours post-TBI.…”
Section: Expression Of Gabaa Receptors Is Modified By Inflammation Anmentioning
confidence: 99%
“…Anesthetic agents acting via GABA A receptors are frequently used in these patients’ anesthesia to induce and maintain general anesthesia. [30] Drexel and coworkers assessed the expression of GABA A receptor subunit mRNAs in rats 6 hours and 4 months post-TBI in the hippocampus and thalamus. [31] In the hippocampus the expression of α1-, α2-, α5-, β2-, β3- γ2- and δ- GABA A receptor subunit mRNAs were down-regulated 6 and 24 hours post-TBI.…”
Section: Expression Of Gabaa Receptors Is Modified By Inflammation Anmentioning
confidence: 99%
“…The positive relationship between neurogenesis and neurological function has long been demonstrated [30, 31]. It is demonstrated that olfactory stimulus induces neurogenesis in the reward circuit, including the amygdala, striatum, entorhinal cortex, and hippocampus [28].…”
Section: Discussionmentioning
confidence: 99%
“…As such, the goal of HBO treatment for acute CO poisoning is the prevention of long-term and potentially permanent neuropsychological dysfunction, in addition to the enhancement of short-term survival rates (7). Emerging evidence indicates the suppression of hippocampal neurogenesis as an important mechanism underlying cognitive impairment associated with traumatic brain injury (13,20,35); therefore, we sought to investigate the hypothesis that early HBO therapy may exert the beneficial effect on acute CO poisoning-induced delayed memory impairment via preservation of neurogenesis. Four lines of evidence derived from the current study support our hypothesis.…”
Section: Discussionmentioning
confidence: 99%